Transição para a sustentabilidade em instituições de ensino superior: um olhar sobre o desenvolvimento sustentável - Tagliaferro , Manoela Pierina (2021)
Faced with the economic, social, environmental, and pandemic crises that make up the world panorama, globally recognized organizations – such as the United Nations Organization and the United Nations Educational, Scientific and Cultural Organization – defend and promote the search for sustainable development as a viable path towards meeting current needs without compromising the future of new generations. In the national context, the Institutions of Higher Education (IHE) hold a social role in higher education for society and must achieve their sustainability in an increasingly competitive market. In view of this reality, the present thesis aimed at identifying the essential dimensions for the Transition to Sustainable Development that encourage Sustainable Development at IHEs. To this end, the research was sustained by the socio-technical transition theory in a multilevel perspective, by the triple bottom line and by sustainable development. In order to meet the exploratory and descriptive objectives of this qualitative research, a multiple case study was chosen with IHEs as the level of analysis to identify the Transition to Sustainable Development initiatives at these institutions as the unit of analysis. The method for data collection in this endeavor used documentary research, bibliographical research, and semi-structured interviews, obtaining primary and secondary data. Content analysis was employed as the method for analysis. The performance of IHEs, with initiatives based on an Education for Sustainable Development in support of meeting the 2030 Agenda for Sustainable Development, is considered a viable thesis to support the process of Transition to Sustainable Development in IHEs. At the end of the data analysis process, IHEs evidently present conditions of adaptability to achieve the Transition to Sustainable Development, having as essential dimensions the need to carry out the Institutionalization, Academic Management and Administrative Management for the process of Transition to Sustainable Development, based on Education for Sustainable Development and on the Sustainable Development Goals. Empirical findings demonstrated that elements imposed by the current regime in which HEIs are inserted – such as regulations, laws, norms – remain as the main drivers of niche initiatives for sustainability. Therefore, if managed according to the aforementioned dimensions, such niche initiatives enable the transformation of IHEs into sustainable organizations.